2017
DOI: 10.1080/13645706.2017.1299763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-incision and conventional laparoscopic surgery for benign adnexal masses

Abstract: SILS seems to be effective and safe for the treatment of benign adnexal masses. SILS appears to be advantageous regarding postoperative pain especially in the early period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The characteristics of these 13 studies, including four RCTs9–12 and nine retrospective studies,13–21 are shown in tables 1 and 2. The geographic distribution of these study institution was varied, with seven reports from Korea, two from Italy and one from America, England, China and Turkey, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of these 13 studies, including four RCTs9–12 and nine retrospective studies,13–21 are shown in tables 1 and 2. The geographic distribution of these study institution was varied, with seven reports from Korea, two from Italy and one from America, England, China and Turkey, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies9–15 19 20 including 846 patients reported perioperative complications. In the pooled analysis, LESS group had more perioperative complications than CL group (6.59% and 2.85%; OR: 2.08; 95% CI: 1.05 to 4.11, p=0.04) (table 3 figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations